De novo malignancies after kidney transplantation - Giuseppina Rosso; Maurizio Salvadori (Giornale di Clinica Nefrologia e Dialisi)
Cancer is the second cause of death in kidney transplant patients in most Western countries. The excess risk of cancer after kidney transplantation is two to three times higher than in the age and sex matched general population. Once cancer develops, the outcome is generally poor, particularly for melanoma, renal cell carcinoma and post-transplant lymphoproliferative disorder. A multidisciplinary approach for screening, prevention, diagnosis and treatment of neoplastic disease after kidney transplantation is necessary.